490 5-Year Follow-up of Periocular Primary Basal Cell Carcinoma at Burnley General Teaching Hospital. (12th October 2021) - Lu, Y; Usmani, H; Fernando, B
Abstract: Aim: (1) To investigate the recurrence rate of periocular primary basal cell carcinoma (pBCC) in Burnley General Teaching Hospital (BGTH). (2) To compare the recurrence rate of periocular pBCC in our centre with the standards published by the British Association of Dermatologists (BAD). Method: A retrospective cohort study was carried out. Inclusion criterion was all patients undergoing surgical excision of periocular pBCC in BGTH between January 2011 to December 2016. Electronic records were reviewed, and the recurrence rate locally was then calculated and compared with the 2% stated in the BAD guidelines [1]. Results: A total of 197 cases met the audit inclusion criteria over the period of 5 years at BGTH. All of them completed 5 years of follow-up. The mean age of the selected population was 75.7 years (SD 12.77). Male:female ratio was 104:93. Only one case was identified as recurrent primary BCC, which makes the recurrence rate of this audit 0.5% (1/197). Conclusions: This audit confirmed that the recurrence rate of periocular pBCC after margin section control achieved the standard set by BAD guidelines. The reason might be that reconstruction is performed after the confirmation of marginal clearance. Although the recommended treatment for pBCC is MMS, it is not available in every centre. However, patients need to wait at least one week for the reconstruction after margin section control. The limitation of this audit includes the data of the size and anatomical site were incomplete for all patients due to inconsistent histology reports.